Mental health reform in the Russian Federation: an integrated approach to achieve social inclusion and recovery - Rachel Jenkins; Stuart Lancashire; David McDaid; Yevgeniy Samyshkin; Samantha Green; Jonathan Watkins; Angelina Potasheva; Alexey Nikiforov; Zinaida Bobylova; Valery Gafurov; David Goldberg; Peter Huxley; et al. (The World Health Organization, 2007)
OBJECTIVE: To facilitate mental health reform in one Russian oblast (region) using systematic approaches to policy design and implementation. METHODS: The authors undertook a three-year action-research programme across three pilot sites, comprising a multifaceted set of interventions combining situation appraisal to inform planning, sustained policy dialogue at federal and regional levels to catalyse change, introduction of multidisciplinary and intersectoral-working at all levels, skills-based training for professionals, and support for nongovernmental organizations (NGOs) to develop new care models. FINDINGS: Training programmes developed in this process have been adopted into routine curricula with measurable changes in staff skills. Approaches to care improved through multidisciplinary and multisectoral service delivery, with an increase in NGO activities, user involvement in care planning and delivery in all pilot sites. Hospital admissions at start and end of the study fell in two pilot sites, while the rate of readmissions in all three pilot sites by 2006 was below that for the region as a whole. Lessons learned have informed the development of regional and federal mental health policies. CONCLUSION: A multifaceted and comprehensive programme can be effective in overcoming organizational barriers to the introduction of evidence-based multisectoral interventions in one Russian region. This can help facilitate significant and sustainable changes in policy and reduce institutionalization.